Evaluation of Cardiotoxicity Using Blood Biomarkers in Breast Cancer and Lymphoma Patients Undergoing Curative Treatment - Mackett, Katharine (My University, 2019)
Objective: To evaluate whether abnormal concentrations in cardiac and inflammatory biomarkers could predict reductions in left ventricular ejection fraction (LVEF) for cancer patients undergoing curative treatment. Materials and Methods: Longitudinal testing was performed for high-sensitivity cardiac troponin I (hs-cTnI), N-terminal pro-B-type natriuretic peptide (NT-proBNP), heart-type fatty acid binding protein (H-FABP) and C-reactive protein (CRP) in HER2+ breast cancer (BC) patients receiving adjuvant trastuzumab treatment (n=22) and in lymphoma patients treated with radiotherapy (n=4). Sex-specific and overall upper limit of normal (ULN) cutoffs were used to identify abnormal results with a reduction in LVEF (<50% and decrease of ≥10% from baseline) indicative of cardiotoxicity. A secondary analysis was performed on the BC patients with normal LVEFs (n=12 with baseline prior to chemotherapy through to 6-months on trastuzumab) with 15 blood collections spaced between 6- and 254-days post-baseline LVEF measurement. Results: A majority of the BC patients had evidence of myocardial injury (hs-cTnI >female ULN=90%) or myocardial dysfunction (NT-proBNP >overall ULN=91%) at any timepoint with fewer patients having abnormal CRP or H-FABP concentrations (H-FABP >ULN=14%; CRP >ULN=45%). Myocardial injury and dysfunction were most evident during the first two cycles of trastuzumab treatment, with myocardial injury also evident during this early timeframe in the female lymphoma patients (3 with hs-cTnI >ULN). In the 12 patients who completed trastuzumab with normal LVEFs (median=60% at 6-months), myocardial injury (hs-cTnI >ULN) and dysfunction (NT-proBNP >ULN) was evident in >50% of patients. Four of the 22 patients did develop cardiotoxicity, but there was no difference in biomarker concentrations between patients with or without cardiotoxicity. Conclusion: The use of the recommended ULN cutoffs identified myocardial injury and dysfunction in a majority of cancer patients in this setting. Biomarker assessments did not relate to cardiac functional imaging studies. Future studies are warranted to assess different cutoffs or biomarker combinations for predicting cardiotoxicity.
Keywords: cardiotoxicity; high-sensitivity troponin; breast cancer; biomarkers